Familial early onset Parkinson's disease caused by a homozygous frameshift variant in PARK7: Clinical features and literature update. (July 2019) - Stephenson, Sarah EM; Djaldetti, Ruth; Rafehi, Haloom; Wilson, Gabrielle R.; Gillies, Greta; Bahlo, Melanie; Lockhart, Paul J.
Abstract: Background: Bi-allelic mutations in PARK7 are a rare cause of autosomal recessive early onset Parkinson's disease (EO-PD). To date, 30 individuals harbouring 20 unique causative variants have been described. Understanding of the spectrum of clinical features and natural history of PARK7 mediated EO-PD remain limited. Methods: We studied a family with three offspring, two of whom were affected with EO-PD. Family members underwent detailed clinical examination and DNA samples from both affected individuals and parents were analysed by exome sequencing. Results: Two brothers of Iranian descent presented at age 29 years with Parkinsonism associated with high-pitched voice and hypomimia. The brothers were followed over a six and fifteen-year period and displayed typical levodopa responsive slowly-progressive Parkinsonism. A novel homozygous frameshift mutation in PARK7 [NM_007262.4:c.90dupG, p(Ile31Aspfs*2)] was identified. Conclusions: Here we report the clinical presentation and progression of EO-PD in brothers with a novel pathogenic PARK7 variant. We expand the clinical phenotype and provide an update of clinical and pathological features of the disorder. Highlights: Bi-allelic mutations in PARK7 cause early-onset recessive Parkinson's disease. Two brothers with a novel homozygous frameshift mutation in PARK7 were identified. Clinical features included high-pitched voice and hypomimia.